The Old Testament : a very short introduction - Coogan, Michael David (Very short introductions, 2008)
The author offers an exploration of the 'Old Testament', illuminating its importance as history, literature, and sacred text. He provides an overview of one of the great pillars of Western religion and culture, a book which remains important today for Jews, Christians, and Muslims worldwide.